Magnetically Driven Living Microrobot Swarms for Aquatic Micro- and Nanoplastic Cleanup - Song, Su-Jin; Kim, Jeonghyo; Gabor, Roman; Zboril, Radek; Pumera, Martin (ACS nano, 2025)
Micro- and nanoplastic pollution is pervasive worldwide, infiltrating drinking water and food chains, accumulating in the human body, and posing serious threats to public health and ecosystems. Despite these urgent challenges, effective strategies to curb the widespread presence of micro- and nanoplastics have not yet been sufficiently developed. Here, we present magnetically driven living bacterial microrobots that exhibit a nature-inspired three-dimensional (3D) swarming motion, allowing the dynamic capture and retrieval of aquatic micro- and nanoplastics originating from various commercial products. By combining autonomous propulsion with magnetically guided navigation, we enabled the multimodal swarming manipulation of magnetotactic bacteria-based living microrobots (MTB biobots). The actuation of a rotating magnetic field induces a fish schooling-like 3D swarming navigation, allowing the active capture of micro- and nanoplastics, which are then retrieved from the contaminated water by magnetic separation. Our results show that the 3D magnetic swarming of MTB biobots synergistically enhances the removal efficiencies of both model and real-world microplastics, demonstrating their practical potential in water treatment technologies. Overall, plastic-seeking living bacterial microrobots and their swarm manipulation offer a straightforward and environmentally friendly approach to micro- and nanoplastic treatment, providing a biomachinery-based solution to mitigate the pressing microplastic pollution crisis.
Keywords: Water Pollutants, Chemical; Robotics; mikroplasty; magnetotactic bacteria; Water Purification; water purification; Magnetic Fields; nanoplastics; microplastics; biohybrid microrobots; magnetické pole; magnetically driven; swarming behavior; Microplastics; čištění vody; chemické látky znečišťující vodu; robotika